Perhitungan aliran dan peramalan karakteristik pompa sentrifugal bertingkat dengan penggunaan CAD blade’s system - W.M. Rumaherang (Department of Mechanical Engineering, University of Udayana, 2008)
An Important problem in centrifugal pumps designing is characteristic works in theoretical calculations. They are precise or very close to practical characteristics and results of tests in laboratory. Hydrodynamics parameters influence on the inlet sides, blades of impeller, vaned diffusers, stage guide vanes and side go out of pump. In turn they have very strong influence on the characteristics. In consequence to the plan of centrifugal pump, an important problem is geometrical constructions of the blades impeller, vaned diffusers, stage guide vanes and outlet of pump. The solution of this problem lays accuracy in hydro dynamical calculations in the design process, manufacturing and installation of pump. Special CAD for the blades can simplify the design process. The obtained result is highly accurate. Sketch can be constructively conducted by AUTOCAD, KOMPAS (KOM?AC) or other programs to determine coordinates of fixed points in the blade lines. All that points are then arranged in formations according to axis r, x, y, z, in the dat.file as input file to CAD. The result presented in the drawing form of blades profile and in the forecasting of whole pumps characteristics: speed, loses, power (N), head (H) and efficiency (?) versus capacity (Q). Calculations made in the several times, get the construction pump with the optimal characteristics. The result indicates that optimal conditions obtain to profile with the main dimensions: impeller dbt=0.065 m, D2=0.240 m, D0=0.1312, z=7, b1=, b2=0.0414 m, ?1=26o, ?s2=23o, ?=103o, diffusers: ?d= ?s4= ?d= ?s5=40o, ?sc= ?bl3=12,0o , ?=40o, stage guide vanes: ?bs= ?s6=89,5o,?= 600.